Enhancing grade eight students’ creative thinking in the water stem education learning unit - Sukaya Sutaphan; Chokchai Yuenyong (Cakrawala Pendidikan: Jurnal Ilmiah Pendidikan)
Water issues, a commonly discussed issue in water STEM education, present students with a challenge to put their engineering design skills to the test in a STEM project. This study aimed to enhance and examine Grade 8 students’ creative thinking in the water STEM education learning unit. It involved purposively selected 45 eight-graders enrolled in a school situated in Khon Kaen, Thailand. The study was carried out in three weeks which equate to twelve hours of learning covered in six lesson plans. Applying the interpretive paradigm, this study adapted Barak and Doppelt (2000)’s Creative Thinking Scale (CTS) to assess students’ applying knowledge and creative thinking. The findings likely demonstrated that most of the portfolio elements may be interpreted for the attainment of creative thinking in layer of awareness, while some others could be viewed layers of observation, strategy, and reflection. This paper clarifies what and how students’ project could be interpreted in each layer of creative thinking. Further implications for setting up STEM education in school setting are proposed.